Transitions through the labor market : work, occupation, earnings and retirement - Polachek, S. W.; Tatsiramos, Konstantinos (Research in labor economics ;, 2018)
Understanding the factors that affect how one transitions from school to the labor market and finally to retirement isimportant both to the individual and to the policy maker. This volume containsseven original and innovative articles that analyze aspects of such labormarket transitions. Questions answered include: How did hiring and firingdecisions change for blacks and Hispanics relative to whites in the GreatRecession? Can redesigning the minimum wage lead to more efficient employmenttransitions and greater social welfare? What are the factors leading a companyto fast-track an employee? How does the number of layers in a companyshierarchical structure affect ones ability to be promoted? Do women gravitateto more socially caring occupations because they care more than men? Doesgaming among youth increase math scores more for boys than girls? And, doesgood health impede ones inclination to retire?